Willingness to Pay for Environmental Service Functions of Mangrove Forest in Uzere, Delta State, Nigeria (2016)
This study was carried out to estimate the value of the environmental service functions of Uzere mangrove forest using the Willingness to pay method. Structured questionnaires were used to obtain information on the willingness to pay (WTP) for environmental service functions of Uzere mangrove forest. Contingent valuation approach was used to elicit information on WTP and the socio-economic variables that influence the WTP. Data were obtained from a systematically sampled 300 residents within the three communities in Uzere. The data were subjected to descriptive statistics, F and student’s t-tests, analysis of variance (ANOVA), correlation and multiple regression analyses using Statistical Package for Social Sciences (SPSS 20). The results show that 21.7% of the respondents were willing to pay (WTP) various amounts ranging from N50 (US$0.33) - N5000 (US$33.33) monthly, N50 (US$0.33) being the modal value. The mean monthly WTP value is N36.8 (US$0.25). This gave an aggregate estimated value of between N147, 835.62 (US$985.57) and N681, 097.19 (US$4540.65) (US$1= N150) for the environmental service functions of the 2,004.2hectares of Uzere mangrove forest. The semi-log regression equation revealed that the years of residence and occupation are the only socio-economic variables that significantly influenced WTP. The results of this study indicate that the forest is of high value and therefore, there is a need for concerted efforts for sustainable management of the mangrove forest